Effect of Soil Management Practices and Slope on Soil Fertility of Cultivated Lands in Mawula Watershed, Loma District, Southern Ethiopia - Damte Balcha Gadana; Parshotam Datt Sharma; Dereje Tsegaye Selfeko (Advances in Agriculture)
Soil degradation is a serious problem challenging food security in Ethiopia. To halt degradation and restore impoverished soils, the government has initiated soil management practices in the affected areas. Still, there is little information on the impact of these practices in terms of improvement in soil fertility of cultivated lands under different soil and climatic conditions. Accordingly, the study was carried out to study the effect of soil management practices, viz, soil bund (SB), application of farm yard manure (FYM), soil bund integrated with FYM (SBFYM), and vis-a-vis no management practice (NM), on soil fertility under upper (20%–30%) and lower (2%–10%) slope ranges at Mawula watershed, Loma district, Southern Ethiopia. Twenty-four composite soil samples (4 practices × 2 slope ranges × 3 sites) drawn from the surface layer (0–20 cm) were analysed for different physical and chemical properties indicative of soil fertility. The data were analysed statistically in a randomized complete block design. All the soil management practices improved significantly the different aspects of physical and chemical fertility (soil texture, bulk density, total porosity, moisture content, organic carbon, and contents of macro and micronutrients, viz, N, P, K, Na, Ca, Mg, Fe, Mn, Zn, and Cu). The practice SBFYM was significantly superior to FYM and SB. The order of performance was SBFYM > FYM > SB > NM. The usefulness of soil management practices was further corroborated by the farmers’ response (based on semistructured questionnaires), as 83% of them perceived the practices well and opted for their adoption. As such, the soil management practices, notably SBFYM, merit their implementation on a large scale to improve fertility and productivity of degraded lands.